Scots pine for fika : the role of local moose density in determining browsing damages to pine across commercial forests in Sweden - Partemi, Rebecca (SLU/Dept. of Ecology, 2022)
By browsing on young Scots pine (Pinus sylvestris), moose (Alces alces) can cause significant damage to commercial forests. The National Forest Agency monitors browsing damage and moose faecal pellet groups annually on pre-defined plots throughout Sweden. Here, we investigated the relationship between moose pellet groups and the proportion of pine trees with fresh (< 1 year) browsing damages. We used mixed-effects logistic regression models with proportion of damaged stems as response and moose pellet group density, presence of other deer pellet groups, Scots pine and birch (Betula spp.) numbers, and site productivity as predictors. We used data collected nationwide and did analyses first for the whole of Sweden and secondly for each separate region by subdividing the same dataset. Overall, the results were consistent across the regions and for Sweden as a whole, with some differences. We found that moose pellet group density was positively correlated with damage in every region and was especially important in explaining damage levels in the north of Sweden. Presence of other ungulates was positively related to pine damage in the Southern region only, and it is unclear to what extent their effect on young pine trees is direct through browsing or indirect through competition. Contrary to recent studies, pine abundance had a secondary role in explaining browsing damage. Instead, browsing damage was positively associated to site productivity and number of birch trees, the latter with a systematic higher importance than moose local density. Plots where birch is abundant might be attractive to moose and therefore indirectly lead to increased browsing damage on pine. Given the consistent positive association found between moose pellet groups and level of damage, we conclude that moose pellet counts on browsing survey plots are an important add-on for the adaptive management of moose and forests. However, pellet count should be made more systematically and should not be limited to young forest stands to properly capture moose density.